A Two-Channel Laser Monitor for Observing Processes of High-Temperature Combustion of Metal Nanopowders - Gubarev F. A. Fedor Aleksandrovich; Mostovshchikov A. V. Andrey Vladimirovich; Ilyin A. P. Aleksandr Petrovich; Li Lin; Fedorov A. I. Anatoly Ignatjevich; Burkin E. Yu. Evgeniy Yurievich; Sviridov V. V. Vitaly Vladimirovich (2021, 2021)
Title screen